Slowing down glioblastoma progression in mice by running or the anti-malarial drug dihydroartemisinin?: induction of oxidative stress in murine glioblastoma therapy - Lemke, Dieter; Pledl, Hans-Werner; Zorn, Markus; Jugold, Manfred; Green, Ed; Blaes, Jonas; Löw, Sarah; Hertenstein, Anne; Ott, Martina; Sahm, Felix; Steffen, Ann-Catherine; Weiler, Markus; et al. (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.10723 Dieter Lemke, Hans-Werner Pledl, Markus Zorn, Manfred Jugold, Ed Green, Jonas Blaes, Sarah Löw, Anne Hertenstein, Martina Ott, Felix Sahm, Ann-Catherine...
Gesehen am 25.06.2020